РЕПРЕЗЕНТАТИВ НУТҚИЙ АКТЛАРНИ ДИСКУРСДА ВОҚЕЛАНТИРИШ УСУЛЛАРИ - Шамахмудова, А.Ф. (SCIENCE and SOCIETY, 2022)
This article deals with the problem of analysing linguistic strategies for implementing the politeness strategies in the Spanish dicourse, that is, the communication strategies used by native speakers in the process of polite communication. The politeness strategies are reflected in the linguistic coding of social partnership and it should be noted that the means of expressing these principles in the language system occur over time, changes in the social environment and in other forms.
Keywords: principle of politeness; positive image; negative image; linguistic strategies; reality; social environment; assertive